Analysis of Relationship between Military Expenditures and Economic Growth - Daněk, Tomáš; Slintáková, Barbora; Ochrana, František, 1952-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The dissertation thesis deals with the relationship between military expenditures and economic growth. The data sample contains European countries and there are three growth models used in the thesis (the Feder-Ram model, the Augmented Solow-Swan model and the Barro model). Two hypothesis and one research question are set in the dissertation. The first hypothesis says that there is a relationship between military expenditures and economic growth. Consequently, the second hypothesis says that the relationship is positive in case of relatively richer countries and negative for relatively poorer countries. Turning to research question, it asks which model better describes the relationship (if it exists) between military expenditures and economic growth.
Vedoucí práce: Barbora Slintáková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations